The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1088/1755-1315/733/1/012091
|View full text |Cite
|
Sign up to set email alerts
|

The phytochemical potential of Averrhoa bilimbi – A review

Abstract: Averrhoa bilimbi grows in tropical and subtropical countries and has the potential to be used as phytopharmaceuticals. Averrhoa bilimbi leaves and fruits contain phytochemicals, such as alkaloids, saponins, tannins, flavonoids, phenols, and triterpenoids. These compounds are mostly obtained by extraction and can be used for their pharmacological properties in the form of antibacterial, antivirus, total cholesterol level reducer, and antioxidant. Further research and development need to be carried out on the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 8 publications
0
16
0
4
Order By: Relevance
“…The phytochemical screening analysis indicated that the leaves of A.bilimbi contained flavonoids, alkaloids, and saponins (Setyawan et al, 2021). Table 1 presents the data of the phytochemical screening test.…”
Section: Results Of Phytochemical Screeningmentioning
confidence: 99%
“…The phytochemical screening analysis indicated that the leaves of A.bilimbi contained flavonoids, alkaloids, and saponins (Setyawan et al, 2021). Table 1 presents the data of the phytochemical screening test.…”
Section: Results Of Phytochemical Screeningmentioning
confidence: 99%
“…Penggunaan bahan bioaktif dari tumbuhan yang potensial digunakan pada pengawetan telur konsumsi adalah daun belimbing wuluh (Averrhoa bilimbi L). Bagian-bagain yang dapat dimanfaatkan dari belimbing wuluh adalah daun, buah, dan akar [5]. Hasil uji fitokimia ekstrak kasar metanol daun belimbing wuluh menunjukkan bahwa daun ini mengandung senyawa-senyawa metabolit sekunder seperti alkaloida, flavonoida, tanin, dan saponin [5,6].…”
Section: Pendahuluanunclassified
“…Bagian-bagain yang dapat dimanfaatkan dari belimbing wuluh adalah daun, buah, dan akar [5]. Hasil uji fitokimia ekstrak kasar metanol daun belimbing wuluh menunjukkan bahwa daun ini mengandung senyawa-senyawa metabolit sekunder seperti alkaloida, flavonoida, tanin, dan saponin [5,6]. Adanya kandungan senyawa metabolit sekunder tersebut maka daun belimbing wuluh memiliki sifat antioksidan [3,4].…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…In general, belimbing wuluh commonly called with starfruit can be used to treat asthma, diabetes, cough, sore throat, canker sores, and fever [5][6][7]. Parts of the belimbing wuluh used for treatment include flowers, leaves, fruit, and stems.…”
Section: Introductionmentioning
confidence: 99%